Modification of gypsum products (Part I): physical and mechanical properties of adding some additives on different types of gypsum products - Nadira A Hatim; Isam K. Al-Khayat; Mohammed A Abdulla (University of Mosul, College of Dentistry, 2007)
Aims: A pilot study was done to evaluate the physical and mechanical properties of the Iraqi plaster (Al- Ahliya gypsum) and Plaster of Paris (British Gypsum), and to improve the quality by the incorporation of some additives. Materials and Methods: Two types of gypsum products were used in this study (Iraqi plaster, Plaster of Paris). Three types of additives {gum arabic at a concentration of (0.1%, 0.25%, 0.35%, 0.50%), calcium oxide at a concentration of (0.1%, 0.25%, 0.35%, 0.50%, 0.75%), and ferric oxide acts as a pigment (blue or red) at a concentration of (0.1%, 0.2%)} were incorporated after preparation into the weighted dried gypsum powder. The effects of these additives on the physical and mechanical properties of the experimental gypsum products (Iraqi plaster and Plaster of Paris) have been evaluated by measuring the water/powder ratio, setting time, linear setting expansion, and compressive strength. Four hundred sixty gypsum samples were prepared for this study. Mean, standard deviation, variance (ANOVA), and Duncan's multiple range tests were used to analyze the measurements. Results: ANOVA showed that there was a significant difference in the water/ powder ratio, setting time, linear setting expansion, and compressive strength between Iraqi plaster and Plaster of Paris depending upon the type and the concentration of each additive used. Conclusions: The last concentration of each additive (gum arabic 0.5%, calcium oxide 0.75%, or ferric oxide 0.2%) in all the experimental measurements that are incorporated within the two gypsum products showed